2016
DOI: 10.1021/acs.cgd.6b01436
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Growth of Methyl Stearate as a Function of Crystallization Environment

Abstract: In situ studies of methyl stearate growing from supersaturated n-dodecane, kerosene, and toluene solutions reveal strong evidence that solvent choice influences the crystal morphology and crystal growth kinetics. Crystals with similar habit are observed in all solvents, with the exception of lower supersaturations in kerosene, where a less symmetric morphology was observed. BFDH analysis based on the monoclinic C2 crystal structure of methyl stearate yielded the morphological indexation to be (110), (1–10), (−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…17 However, the enhanced supersaturations that are often employed in solution crystallisation and variations in crystalline surface chemistries, can result in different crystalline surfaces growing according to different growth mechanisms, which can strongly impact upon the resultant 'as grown' crystal morphology. 1,22,23 Though there has been some evidence for some surface reconstruction of conformationally flexible molecules, 24 the surface to bulk equivalence assumption has been effectively used to model the crystal morphology of organic materials. 12,14,19,[25][26][27] However, molecular modelling techniques have been developed to calculate bulk solution and interfacial intermolecular interactions of a crystal in contact with a solution, 28,29 hence attempting to address the equivalent wetting and proportionality assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, the enhanced supersaturations that are often employed in solution crystallisation and variations in crystalline surface chemistries, can result in different crystalline surfaces growing according to different growth mechanisms, which can strongly impact upon the resultant 'as grown' crystal morphology. 1,22,23 Though there has been some evidence for some surface reconstruction of conformationally flexible molecules, 24 the surface to bulk equivalence assumption has been effectively used to model the crystal morphology of organic materials. 12,14,19,[25][26][27] However, molecular modelling techniques have been developed to calculate bulk solution and interfacial intermolecular interactions of a crystal in contact with a solution, 28,29 hence attempting to address the equivalent wetting and proportionality assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we should comment on the almost identical lattice parameters of form IV identified in this study and the monoclinic form reported in ref. 18. The only difference is in the assignment of space group (C2/c for form IV compared with C2 in the previous report).…”
Section: Identification Of a Further Phasementioning
confidence: 74%
“…However, no further structural details were reported. 18 Form II contains one molecule in the asymmetric unit. There are four molecular layers in the unit cell, packed in a tilted manner and forming roof-like "ripples" along the c-axis (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…3, it can be seen that the diffusion related term with a value of 8.65  10 -4 is over 2 times magnitude larger than that for the surface integration term (5  10 -6 ). Therefore the rate of crystal growth of face {011} is diffusion limited by diffusion mass transfer (Camacho et al, 2016), i.e. the crystal growth is controlled by how fast the solute molecules in bulk solution diffuses from the bulk solution and across the solid/solution boundary layer for integrating with (growing on) the crystal face.…”
Section: Solubility and Facet Growth Ratesmentioning
confidence: 99%